The Influence of Politically Connected Directors on Audit Quality of Quoted Firms in Nigeria. - Oriakhi, Solomon; Simire, Cyril O. (The Journal of Accounting and Management, 2023)
This study examined the influence of politically connected directors on audit quality of quoted firms in Nigeria.The variable of politically connected directors (POCD) wasanalysed to determine the nexus with audit quality (AUDQ). For the objective of the study to be achieved, a total of twenty two (22)non-financialfirmsquoted on the Nigerian Exchange Group (NXG) as at 2020 were selectedcarefully and analysed for a period (2015-2020). Thepanel regression was used with the help of Eview 9.0 econometric packages for dataanalysis. The result revealed that the independent variable of politically connected directors (POCD) had a positive and significant influence on audit quality (AUDQ) of non-financial quoted firms in Nigeria at the level of 5%. The study therefore recommendsthat politically connected directors should be encouraged because it enhances audit quality of non-financial quoted companies. The studysuggested that future studies should also work on other corporate governance variables to investigate the influence on audit quality.